The birthplace and relative age effects in Brazilian olympic athletes: a cross-national comparison - Thuany, Mabliny; Vieira, Douglas; Lima, Marcos; Cavalcante, Jaíne Taniele; Alcântara, Tatiana; Nikolaidis, Pantelis T.; Knechtle, Beat; Weiss, Katja; Gomes, Thayse Natacha (Frontiers in Psychology, 2023)
Purpose Our purpose was to verify the existence of birthplace and relative age effect (RAE), as well as the association between birthplace effect and RAE among Brazilian athletes competing in the Olympic Games. Methods Data included information about Brazilian Summer Olympic athletes from 1920 to 2021. To investigate RAE, athletes’ birthdate was distributed into birth quartiles (Q1: Jan–Mar; Q2: Apr–Jun; Q3: Jul–Sep; Q4: Oct–Dec), while birthplace effect was assessed considering the state and the region (Southeast; Northeast; South; North; and Midwest) of birth. The Chi-square test (χ2) was used to verify differences between the birthplace effect and RAE. Results The sample consisted of 388 Brazilian athletes of both sexes, distributed in 38 sports modalities from 23 Brazilian states (Southeast = 66.5%; South = 14.4%; Northeast = 12.1%; North = 1.5%; Midwest = 5.4%). For both sexes, most of the athletes were from the São Paulo state (37.4%), followed by Rio de Janeiro (18.3%), both from the Southeast region. For birthdate distribution according to birthplace, it was observed that the North region presented the highest frequency of athletes born in Q1 (50%), followed by the Northeast and Southeast regions. No significant differences were found for the birthplace effect (χ2 = 5.69, value of p = 0.128) and RAE between sexes (χ2 = 0.530, value of p = 0.912), nor was shown an association between the birthplace effect and RAE. Conclusion Most Brazilian Olympic athletes are from the Southeast region, but no RAE was established regarding their birthplace. Results from the present study can guide sports public policies in Brazilian regions, especially in the Midwest, North, and Northeast regions, which are underrepresented in Brazilian high-performance sports.